(untitled) (Experimental biology, 2018)
Poly(ADP-ribose) polymerases (PARPs) catalyse the synthesis of polymers of ADP-ribose (PAR) covalently attached to acceptor proteins using nicotinamide adenine dinucleotide (NAD+) as a substrate. The genome of Arabidopsis thaliana, a widely used model plant organism, encodes at least three putative PARPs: AtPARP1 (At4g02390), AtPARP2 (At2g31320) and AtPARP3 (At5g22470). There is evidence that plant PARPs are structurally homologous to mammalian PARP proteins. The high degree of conservation at the amino acid level between Arabidopsis and mammalian forms of these enzymes suggests that PARP function is conserved between plants and animals. Plant PARPs also have enzymatic activities that are functionally homologous to mammalian PARPs. In contrast to mammalian systems, surprisingly very little is known about PARPs-catalyzed PARylation in plants. Here, we isolated the AtPARP2 cDNA gene encoding the Arabidopsis thaliana Poly(ADP-ribose) polymerase 2 using the reverse transcription - polymerase chain reaction (RT-PCR). AtPARP2 with a 6xHis end was functionally expressed in E. coli and purified by nickel affinity chromatography. Amino acid sequencing of the putative recombinant protein by MALDI-TOF MS and its analysis using NCBI BLAST indicated that the enzyme belongs to poly (ADP-ribose) polymerases family. It was revealed that the product of gene expression is a globular protein with a mass of 72 kDa, consisting of 637 amino acids (pI 5.92). Purified AtPARP2 was used as an immunogen to generate rabbit polyclonal anti- AtPARP2 antibodies. A specific AtPARP2 reaction using an oligonucleotide duplex containing a chain break to activate the poly ADP-ribosylation process in the presence of NAD showed the auto-poly-ADP-ribosylation activity of recombinant proteins. Key words: Poly(ADP-ribose) polymerase, PARP2, poly-ADP-ribosylation, NAD+, reactive oxygen species, Arabidopsis thaliana.